Swertia drassensis, a new species from Drass, Ladakh Himalaya - Banoo, Sakina; Anzar Ahmad Khuroo; Aijaz Hassan Ganie (Phytotaxa, 2022)
Swertia drassensis (Gentianaceae) is described as a new species from Drass, an area located in the Trans-Himalaya region of Ladakh, India. This new species resembles in few characters to its congeneric Swertia petiolata, but clearly differs from it in possessing a pair of fused nectaries, fimbriae characteristically absent, margin of sepals slightly membranous, greenish-yellow, ovoid-ellipsoid capsule and winged seeds. Photo-illustrations and comparison of diagnostic characters of the new species with other congeneric species are provided to facilitate field identification.